All Questions Topic List
Differentiation Questions
Previous in All Question Next in All Question
Previous in Differentiation Next in Differentiation
Question Number 134108 by Eric002 last updated on 27/Feb/21
ddx(x3+1x3−14)
Answered by Ñï= last updated on 27/Feb/21
ddx(x3+1x3−14)=ddxe14lnx3+1x3−1=ddxe14ln(x3+1)−ln(x3−1)=x3+1x3−14[14(3x2x3+1−3x2x3−1)]
Answered by EDWIN88 last updated on 28/Feb/21
lety=x3+1x3−14y4=x3+1x3−1⇒lny4=ln(x3+1)−ln(x3−1)4y.y′=3x2x3+1−3x2x3−1=3x2(−2x6−1)y′=−3x22(x6−1).x3+1x3−14.―
Answered by MJS_new last updated on 28/Feb/21
ddx[h(f(x)g(x))]=h′(f(x)g(x))×ddx[f(x)g(x)]==h′(f(x)g(x))×f′(x)g(x)−f(x)g′(x)g(x)2ddx[(x3+1x3−1)1/4]=14(x3+1x3−1)−3/4×3x2(x3−1)−(x3+1)3x2(x3−1)2==14(x3−1x3+1)3/4×−6x2(x3−1)2==−3x22(x3+1)3/4(x3−1)5/4
Terms of Service
Privacy Policy
Contact: info@tinkutara.com